Analisis Peran Guru Dalam Upaya Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas III Di SDN 08 Bungkang - Vikram Yuda Octa Firandhi, Yuli Budhiarti, Normala (LPPPI Publishing, 2023)
The background of this research is that there are still grade III students who have not been able to read well, students' reading abilities are still in recognizing letters, and a lack of attention to students who experience these problems. beginning reading for class III students at SDN 08 Bungkang This research method is a qualitative method with a qualitative descriptive approach. Collecting data using interview techniques, questionnaires and documentation. Subjects and research objects of class III teachers and class III students with a total of 10 students consisting of 4 male students and 6 female students. The data analysis technique uses 3 stages, namely, data reduction, data presentation and conclusion. The research results by analyzing 6 indicators of the teacher's role, namely, the teacher as educator, teacher, mentor. directors, trainers and assessors showed that of the 6 indicators of the teacher's role it was still lacking in its application, because there were several inhibiting factors for teachers and students in the learning process. The barrier factor is the lack of learning media (books) for the ease of student learning. The conclusion of this study is that the level of application of the teacher's role in an effort to improve the reading ability of the beginning graders of class III SDN 08 Bungkang is classified as